β-1,3-glucan effect on the defence reaction of tomato leaves under fusarium wilt - Kabashnikova, Liudmila; Shpileuski, Sviataslau; Domanskaya, Irina; Loucsha, Victoria (Journal of the Belarusian State University. Ecology, 2024)
Objective reasons for a significant reduction in tomato crop yield include infection with pathogens of fungal diseases. In this regard, the study of the structural and functional characteristics of an infected plant represents an important step towards elucidating the mechanisms of resistance and creating a system of effective protection against diseases of fungal etiology. The effect of a drug containing β-1,3-glucan and a water-soluble polymer (WSP) based on a copolymer of acrylamide with sodium acrylate on the development of the pathogenic fungus Fusarium oxysporum sp. (Fus.oxy.) on solid Czapek medium was studied. The formation of protective reactions occurring in the leaves of 60-day-old tomato plants (Lycopersicon esculentum Mill., variety Tamara) during artificial Fusarium infection was studied under laboratory conditions. An assessment of the effect of β-1,3-glucan and WSP on the growth of fungal mycelium showed that the area of fungal colonies increases relative to the control variant by 4.0 and 4.7 times, respectively, therefore these compounds do not have antifungal activity and, moreover, stimulate the growth of fungal colonies in vitro. The protective effect of a preparation containing β-1,3-glucan and WSP was studied by pre-spraying tomato plants that were transferred from soil culture to tap water and infected with spores of the fungus Fus. oxy. through the root system. It was found that treatment of tomato plants with β-1,3-glucan induces protective reactions, which are characterized by an increase in the content of reactive oxygen species, polyphenols and anthocyanins against the background of an increase in the expression of genes for PR proteins − β-1,3-glucanase (Glu) and chitinase (Chi) in tomato leaves during infection with Fus. oxy. Quantitative analysis of the content of photosynthetic pigments showed that the pathogenic fungus has a negative effect on the pigment apparatus, reducing the content of chlorophylls and carotenoids in tomato leaves, while pre-treatment of plants with a preparation including β-1,3-glucan and WSP contributes to a significant increase in the content of photosynthetic pigments. The results obtained provide a scientific basis for the use of β-1,3-glucan in crop production to improve the disease resistance of tomato plants.